Adam und Eva: Michel Foucaults ominöser "vierter Band" schließt endlich die Histoire de la sexualité ab. Issue 1 (22nd May 2018) - Sarasin, Philipp
The forth volume of Foucault's Histoire de la sexualité, only recently edited by Frédéric Gros, sets the keystone not only to his "history of sexuality, " but to his entire work. Though the reading of the book with all its scholarly details of early Christian theology might appear quite challenging, it reveals clearly how Foucault's own thinking has changed from 1977 onwards. His reading of the church fathers showed him, on the one hand, the genealogical roots of Lacan's concept of the "subject of desire" as a "subject of the law, " and, on the other hand, its "counterpoint" (as Frédéric Gros puts it): the Greek and Roman techniques of the self. Hence, while Foucault has operated, in the first volume of his History of Sexuality (1976 ), with the dichotomy law vs. norm, the new (and final) distinction was law vs. techniques of the self.